Successful eculizumab treatment as an adjunctive therapy to desensitization in ABO-incompatible living donor kidney transplantation and its molecular phenotypes - Heo, Ga Young; Jung, Minsun; Piao, Honglin; Kim, Hyun Jeong; Kim, Hyung Woo; Lee, Juhan; Huh, Kyu Ha; Kim, Beom Seok; Yang, Jaeseok (Frontiers in Immunology, 2024)
Introduction: ABO-incompatible (ABOi) kidney transplantation (KT) has become an important option to overcome organ shortage. Plasmapheresis/rituximab-based desensitization therapy has successfully reduced anti-ABO antibody levels and suppressed antibody-mediated rejection (AMR) in ABOi KT. However, high titers of anti-ABO antibodies in some patients are refractory to standard desensitization, leading to loss of KT opportunities or AMR.Methods: Eculizumab treatment was used an adjunctive therapy to rescue high-titer ABOi KT patients refractory to plasmapheresis/rituximab-based desensitization. Molecular phenotypes of allograft biopsies and cellular phenotypes of peripheral blood mononuclear cells of eculizumab group were compared with those of control groups using the Banff Human Organ Transplant gene panel and flow-cytometric analysis, respectively.The initial titers of anti-ABO antibodies in the two patients were 1:512 and >1:1024; the final pre-transplant titers after desensitization were 1:128 and 1:64. Both patients received eculizumab from KT day to two or four weeks post-KT and maintained stable renal function up to one-year post-transplantation without overt infection, despite early episodes of probable AMR or borderline T cell-mediated rejection. Molecular phenotype analysis revealed that gene expression patterns in the ABOi KT with eculizumab group overlapped with those in the ABOi KT with AMR group more than in the ABOi KT without AMR group, except for complement pathway-related gene expression. Anti-ABO antibody titers decreased to low levels 1-3 months post-transplant in the eculizumab group in parallel with decreasing anti-B-specific B cells.Conclusions: Short-term eculizumab therapy is promising for rescuing ABOi KT recipients with high anti-ABO antibody titers refractory to plasmapheresis-based desensitization therapy.